Mountain Jews in Kabardino-Balkaria: Problems of Socioeconomic Development and Emigration - Alim, Tetuev (Kavkazologiya, 2025)
The article comprehensively examines the problems of socio-economic development of the Mountain Jewish community in Kabardino-Balkaria in the 1920s–1980s and the reasons for their emigration in the late 1990s. It summarizes the experience of the Executive Committee of the Soviets of the Mountain Jewish Colony in organizing the cooperation of leather-working artisans into production cooperatives and agricultural partnerships. The article also identifies the number of dispossessed and repressed Mountain Jews. The community's efforts to eliminate illiteracy, as well as its efforts to develop education, culture, and the formation of a national intelligentsia, have been studied. The article explores the participation of Mountain Jews in the Great Patriotic War. It also examines the socio-economic development of the Mountain Jewish community in the Kabardino-Balkarian Republic in the post-war period, during the years of perestroika, and in the post-Soviet era. Our research suggests that the democratic transformations that took place in the post-Soviet space in the 1980s and 1990s created favorable conditions for the Mountain Jews to freely choose their country of residence. As a result, a significant number of Mountain Jews began to leave the Kabardino-Balkarian Republic. The reasons for emigration have been identified, and the main ones are Israel's policy aimed at uniting the Jewish nation and the desire of the Mountain Jews to live in their historical homeland.